Molecular identification and enzymatic profiling of Trypodendron (Curculionidae: Xyloterini) ambrosia beetle-associated fungi of the genus Phialophoropsis (Microascales: Ceratocystidaceae). (April 2019) - Lehenberger, Maximilian; Biedermann, Peter H.W.; Benz, J. Philipp
Abstract: Ambrosia fungi are a polyphyletic group from currently seven ascomycete and basidiomycete lineages that independently evolved an obligate farming mutualism with wood-boring weevils. One long known, but understudied, association is the mutualism between the scolytine beetle genus Trypodendron (Curculionidae: Xyloterini) and the Microascales fungal genus Phialophoropsis (Ascomycota: Ceratocystidaceae) for which a species-specific association has not been safely established yet. Moreover, the fungal wood degrading capabilities are completely unknown. Here, the ambrosia fungi of three Xyloterini species, Trypodendron domesticum, Trypodendron lineatum and Trypodendron signatum, were isolated and identified using culture-dependent methods. T. lineatum was confirmed to be exclusively associated with Phialophoropsis ferruginea, whereas T. domesticum and T. signatum are associated with a closely related but putatively novel Phialophoropsis species. Investigations of their wood decomposing potential revealed that both fungi mainly depolymerize xylan but are weak mannan decomposers. In addition, robust cellulolytic activity was observed, indicating cellulose as another main carbon source.